PEMANFAATAN HERBA SELEDRI (Apium graveolens L.) UNTUK MENURUNKAN KOLESTEROL DAN LIPID DALAM DARAH TIKUS PUTIH YANG DIBERI DIIT TINGGI KOLESTEROL DAN LEMAK - Juheini, Juheini (Makara Journal of Science, 2002)
It has been known that celery herbs (Apium graveolens L) contain unsaturated fatty acid, so it could be used as hypocholesterolemia and hypolipidemia agents. A study about the effect of celery herbs juice to cholesterole and lipid blood concentration high feeding cholesterol and lipid diet white rat, has been carried out. In this observation, 30 (thirty) male white rats with 150 to 200 g of weight and 4 months of age were used and divided into five groups randomly. The first group was as a normal control, the second group was given high cholesterol and lipid diet 2,5 g/200 g bow (body weight)/day as a treatment control. For the third, the fourth and the fifth groups, each of them was given with high cholesterol and lipid diet in the same quantity with the second group and get celery herb juice with 0,14 g/200 g bow/day; 0,72 g/200 g bow/day; 3,6 g/200 g bow/day dosage. After six weeks of treatment, the rats were surgeried, the blood was taken out from the heart and then total cholesterol and total lipid concentration were measured. The results showed that all of dosages of celery herb juice has lowering cholesterol and lipid effects, but did not decrease the total cholesterol and total lipid concentration significantly.